Leviathan and the Myograph: Hermann Helmholtz's "Second Note" on the Propagation Speed of Nervous Stimulations. Issue 3 (10th August 2015) - Schmidgen, Henning
Argument In the winter of 1849–1850 in Königsberg, German physiologist Hermann von Helmholtz (1821–1894) conducted pioneering measurements concerning the propagation speed of stimulations in the living nerve. While recent historians of science have paid considerable attention to Helmholtz's uses of the graphic method, in particular his construction of an instrument called "myographion, " this paper draws attention to the inscription surfaces that he used in effective ways for capturing and transmitting his findings. Against the background of recent archival findings, I show that Helmholtz used isinglass copies of his graphical recordings in order to communicate the basic principle of previous measurements to the academic public. As the correspondence with his Berlin-based friend and colleague Emil du Bois-Reymond (1818–1896) and the subsequent development of the myographion make clear, these curves were not meant as measurements but functioned as demonstrations. In other words, Helmholtz's curves did provide "images of precision" (Olesko and Holmes 1993) – but they were not precise images.